Evidence for a positron-exciton insulator in alkali-halide crystals - Vorobyev А. А. Alexander Akimovich (1976, 1976)
The angular correlation of annihilation photons for single crystals of 60% KCl-40% KBr solid solutions and X-irradiated NaBr crystals were measured. For 60% KCl-40% KBr samples the measurements of the angular correlation curves were carried out under an external magnetic field of 13.0 kG. The experimental data and theoretical estimations show that thermalized positrons, captured by free cation vacancies, form the positron centre of F4-type; if the positrons are localized near the complex defects, containing the cation vacancies, the formation of peculiar “positron-exciton complex” of the positronium-like type is realized.